2021
DOI: 10.1088/1361-6668/abc7f5
|View full text |Cite
|
Sign up to set email alerts
|

The inverse proximity effect in strong ferromagnet–superconductor structures

Abstract: The magnetization in a superconductor induced due to the inverse proximity effect is investigated in hybrid bilayers containing a superconductor and a ferromagnetic insulator or a strongly spin-polarized ferromagnetic metal. The study is performed within a quasiclassical Green function framework, wherein Usadel equations are solved with boundary conditions appropriate for strongly spin-polarized ferromagnetic materials. A comparison with recent experimental data is presented. The singlet to triplet conversion … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 43 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…In typical experimental systems the superconductor is disordered, so disorder effect on pairing potential needs to be considered, see, e.g., Ref. [56]. Furthermore, in recent experiments S and F layers are separated by an intermediate spacer layer, which significantly reduces this inverse proximity effect.…”
Section: B Superconducting Transport: Scattering Matrix Approachmentioning
confidence: 99%
“…In typical experimental systems the superconductor is disordered, so disorder effect on pairing potential needs to be considered, see, e.g., Ref. [56]. Furthermore, in recent experiments S and F layers are separated by an intermediate spacer layer, which significantly reduces this inverse proximity effect.…”
Section: B Superconducting Transport: Scattering Matrix Approachmentioning
confidence: 99%
“…Earlier, we have shown that the induced magnetization almost does not depend on the precession frequency [ 29 ]. This is because the absolute value of the projection of the magnetization vector to the interface plane does not change with a change of the precession frequency and may be given by the stationary component of the induced magnetization [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The first plausible example of the emergence of TSC was observed in Cu x Bi 2 Se 3 during transport and spectroscopic studies. SnTe and its composites and heterostructures are more prominent candidates for potential applications such as thermoelectrics, ultralow-power dissipation spintronics and quantum computing applications [16,17] using the magnetic and superconductivity proximity effect (SCPE). Rich physics has been observed in topological materials at the TI/ferromagnetism (FM) and TI/superconductor (SC) interfaces due to spinorbit torque/spin transfer torque [18] and Rashba spin-orbit interaction [19].…”
Section: Introductionmentioning
confidence: 99%